Structural, thermal and physico‑chemical properties of high density polyethylene/natural rubber/modified cassava starch blends - Kahar, A.M.W.; Sarifuddin, Norshahida; Ismail, Hanafi (Springer International Publishing AG. Part of Springer Nature., 2017)
t The utilization of cassava starch as one of the components in high density polyethylene (HDPE)/natural rubber (NR) blends were investigated. The true challenge in producing new materials based on natural resources is to design materials that could level the mechanical properties of existing conventional polymers. In this study, we have focused on characterizing the HDPE/NR blends incorporated with cassava starch in the form of granulates (native and silanized) as well as plasticized starch. Cassava starch acted as a biodegradation component in the HDPE/NR blends and the incorporation of cassava starch reduced thermal stability and the degree of crystallinity in general. Several series of cassava starch modifications were performed in order to improve the final properties of the blends. Cassava starch was treated with a silane coupling agent, and proved to be effective in improving tensile strength. The better dimensional stability and compatibility between the blend phases were obtained in the silanetreated cassava starch, as observed in the dynamic mechanical analysis results. Cassava starch was also converted into a plasticized form (TPS), and from the results, the degree of TPS adhesion at the inter-phase ofthe HDPE/NR-TPS blend was clearly improved, as indicated in the morphology study. Through the comparison of thermal degradation results, the HDPE/NR/TPS blends proved to be superior to the HDPE/NR/particulate starch counterparts.